2019
DOI: 10.1097/shk.0000000000001259
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induction Ameliorates Inflammatory Responses in Intestinal Ischemia–Reperfusion Through Inhibiting NLRP3 Inflammasome Activation

Abstract: Intestinal ischemia/reperfusion (I/R)-induced systemic inflammation leads to multiple organ dysfunction syndrome. Previous studies have indicated that the NOD-like receptor protein (NLRP)3 inflammasome modulates intestinal inflammation; however, the pathophysiological mechanisms remain unclear. Autophagy is a critical metabolic mechanism that promotes cellular survival following ischemic injury. Recently, basal autophagy has been implicated in the alleviation of extensive inflammation. However, the role of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…It has been reported that PINK1-Parkin-mediated mitochondrial autophagy played a protective role in CI-AKI by reducing NLRP3 inflammasome activation 38 . Autophagy, by inhibiting NLRP3 inflammasome activation, could alleviate intestinal I/RI and the inflammatory response 20 . The present study showed that autophagy in the myocardium of 8-week-old diabetic rats was significantly inhibited, accompanied by activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PINK1-Parkin-mediated mitochondrial autophagy played a protective role in CI-AKI by reducing NLRP3 inflammasome activation 38 . Autophagy, by inhibiting NLRP3 inflammasome activation, could alleviate intestinal I/RI and the inflammatory response 20 . The present study showed that autophagy in the myocardium of 8-week-old diabetic rats was significantly inhibited, accompanied by activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autophagy can also reduce inflammation by eliminating inflammatory stimuli, such as ROS, mitochondrial deoxyribonucleic acid or damaged organelles, to maintain homeostasis 17,18 . Previous observations found that autophagic activity can attenuate cerebral and intestinal I/RI by eliminating mitochondrial deoxyribonucleic acid and mitochondrial ROS, and inhibiting the activation of NLRP3 inflammasome 19,20 .…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have demonstrated that NLRP3 inflammasome involved in several ischemia reperfusion injury organ such as heart, liver, kidney and so on. Interestingly, little has been reported about the role of NLRP3 in intestinal ischemia-reperfusion injury until Wang et al identified that NLRP3 actually count in intestinal IRI [30]. Several studies suggested that targeting inhibiting NLRP3 inflammasome activation could alleviate ischemia reperfusion injury occurring in different organs [11-13, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that NLRP3 inflammasome involved in several ischemia reperfusion injury organ such as heart, liver, kidney and so on. Interestingly, little has been reported about the role of NLRP3 in intestinal ischemia-reperfusion injury until Wang et al identified that NLRP3 actually count in intestinal IRI [30]. Several studies suggested that targeting inhibiting NLRP3 inflammasome activation could alleviate ischemia reperfusion injury occurring in different organs [7,12,13,31,32].…”
Section: Discussionmentioning
confidence: 99%